Comparing an Emotion- and a Behavior-Focused Parenting Program as Part of a Multsystemic Intervention for Child Conduct Problems. Issue 3 (3rd May 2016) - Duncombe, Melissa E.; Havighurst, Sophie S.; Kehoe, Christiane E.; Holland, Kerry A.; Frankling, Emma J.; Stargatt, Robyn
Abstract : This study evaluated the effectiveness of a multisystemic early intervention that included a comparison of an emotion- and behavior-focused parenting program for children with emerging conduct problems. The processes that moderated positive child outcomes were also explored. A repeated measures cluster randomized group design methodology was employed with three conditions ( Tuning in to Kids, Positive Parenting Program, and waitlist control) and two periods (preintervention and 6-month follow-up). The sample consisted of 320 predominantly Caucasian 4- to 9-year-old children who were screened for disruptive behavior problems. Three outcome measures of child conduct problems were evaluated using a parent (Eyberg Child Behavior Inventory) and teacher (Strengths and Difficulties Questionnaire) rating scale and a structured child interview (Home Interview With Child). Six moderators were assessed using family demographic information and a parent-rated measure of psychological well-being (Depression Anxiety and Stress Scales short form). The results indicated that the multisystemic intervention was effective compared to a control group and that, despite different theoretical orientations, the emotion- and behavior-focused parenting programs were equally effective in reducing child conduct problems. Child age and parent psychological well-being moderated intervention response. This effectiveness trial supports the use of either emotion- or behavior-focused parenting programs in a multisystemic early intervention and provides greater choice for practitioners in the selection of specific programs.